Fertilidade de solo e viabilidade técnica - econômica da agricultura de precisão na Região das Missões - RS - Schadeck, Flavio André (2015)
This paper presents a study that was conducted in a commercial area of grain production in the municipality of Santo Ângelo, region of the Missions - northwest of Rio Grande do Sul, during the Master Course in Precision Agriculture, Federal University Santa Maria / UFSM. The Climate is second Köppen classification of humid subtropical Cfa and gently undulating, with a fertility for the nutrient phosphorus (P) already built. This study aimed to determine whether use of precision agriculture tools, by applying fertilizers correction broadcasted with the variable rate shows an increase in soil fertility levels, and to verify the yield of soybean and wheat over three years subsequent and its technical and economic viability. The Trial period was set for the months of June 2011 to June 2014. Methodologically the project had an applied research, quantitative nature, from the point of view of its objectives was contemplating a descriptive case study. technical and economic. The Soil analyzes were performed by BaseAP Company, highlighting the main variables pH soil, Saturation for bases and potassium with need correction. Obtained was a 43% reduction in the use of lime and an increase in soybean and wheat productivity between 19 and 28%. The study showed an economic return to the producer of 22% compared to a control area without Precision Agriculture. It was expected an increase in the potassium concentration in the resampling but not found, raising the possibility of doing a maintenance fertilization on crop instead of making a soil amendment.